Pharmacogenomics as a Tool to Limit Acute and Long-Term Adverse Effects of Chemotherapeutics: An Update in Pediatric Oncology - Bernsen, Emma C.; Hagleitner, Melanie M.; Kouwenberg, Theodorus W.; Hanff, Lidwien M. (Frontiers in Pharmacology, 2020)
In the past decades, new cancer treatments have been introduced in pediatric oncology leading to improvements of clinical outcome and survival rates. Nevertheless, there are inter-individual differences in efficacy and toxicity of cancer treatments among children. An explanation for these differences is genetic variations between patients, resulting in different drug metabolizing and transport enzymes expression and activity as well as differences in drug targets. Pharmacogenetic testing has emerged as a promising tool to predict and limit acute and long term adverse effects in patients. However, in pediatric oncology, a limited number of patients and a considerable diversity in study results complicate the interpretation of test results and its clinical relevance. In this review a selection of articles generated from terms related to pediatric oncology, pharmacogenomics, pharmacogenetics and adverse effects of (pediatric) cancer drugs. We included 130 studies assessing the association between genetic variations and chemotherapeutic toxicities. The following chemotherapeutics and their toxicities are discussed: alkylating agents, anthracyclines, asparaginase, methotrexate, platinum compounds, steroids, thiopurines, topoisomerase inhibitors and vinca alkaloids. Most research was performed in patients with acute lymphatic leukemic (ALL). With this review, we provide an overview of new developments over the past years regarding relevant polymorphisms related to drug safety in pediatric oncology.